PEMAHAMAN KEBERAGAMAAN DAN GERAKAN KELOMPOK FPI SURABAYA - Syamsul Ma’arif (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2012)
Attitudes of FPI (Islamic Defenders Front) in Indonesia so far impressed 'frontal' and against any form of indecent behavior. Their action, in fact it can be said as one of the deepest expression of a group of Muslims in articulating religious teachings are embraced, or as an attitude of